Early High-dosage Atorvastatin Treatment Improved Serum Immune-inflammatory Markers and Functional Outcome in Acute Ischemic Strokes Classified as Large Artery Atherosclerotic Stroke: A Randomized Trial. Issue 13 (March 2016) - Tuttolomondo, Antonino; Di Raimondo, Domenico; Pecoraro, Rosaria; Maida, Carlo; Arnao, Valentina; Corte, Vittoriano Della; Simonetta, Irene; Corpora, Francesca; Di Bona, Danilo; Maugeri, Rosario; Iacopino, Domenico Gerardo; Pinto, Antonio
Abstract : Abstract: Statins have beneficial effects on cerebral circulation and brain parenchyma during ischemic stroke and reperfusion. The primary hypothesis of this randomized parallel trial was that treatment with 80 mg/day of atorvastatin administered early at admission after acute atherosclerotic ischemic stroke could reduce serum levels of markers of immune-inflammatory activation of the acute phase and that this immune-inflammatory modulation could have a possible effect on prognosis of ischemic stroke evaluated by some outcome indicators. We enrolled 42 patients with acute ischemic stroke classified as large arteries atherosclerosis stroke (LAAS) randomly assigned in a randomized parallel trial to the following groups: Group A, 22 patients treated with atorvastatin 80 mg (once-daily) from admission day until discharge; Group B, 20 patients not treated with atorvastatin 80 mg until discharge, and after discharge, treatment with atorvastatin has been started. At 72 hours and at 7 days after acute ischemic stroke, subjects of group A showed significantly lower plasma levels of tumor necrosis factor-α, interleukin (IL)-6, vascular cell adhesion molecule-1, whereas no significant difference with regard to plasma levels of IL-10, E-Selectin, and P-Selectin was observed between the 2 groups. At 72 hours and 7 days after admission, stroke patients treated with atorvastatin 80 mg in comparison with stroke subjects not treated with atorvastatin showed a significantly lower mean National Institutes of Health Stroke Scale and modified Rankin scores. Our findings provide the first evidence that atorvastatin acutely administered immediately after an atherosclerotic ischemic stroke exerts a lowering effect on immune-inflammatory activation of the acute phase of stroke and that its early use is associated to a better functional and prognostic profile.